Trends of mortality due to breast cancer in Poland, 2000-2016 - Monika Burzyńska; Irena Maniecka-Bryła; Małgorzata Pikala (BMC, 2020)
Abstract Background The aim of the study was to assess trends in mortality and the number of lost years of life due to breast cancer in the female population in the years 2000-2016, with consideration given to differences regarding the level of education and place of residence. Methods The analysis was based on a database of the Central Statistical Office of Poland, containing information gathered from 92,154 death certificates of all Polish female inhabitants who died in the period 2000-2016 due to breast cancer. The SEYLLp (Standard Expected Years of Life Lost per living person), the SEYLLd (per deaths), the APC (Annual Percentage Change), the AAPC (Average Annual Percentage Change) were calculated to determine years of life lost. Results The mean age of women who died from breast cancer increased in the study period from 64.7 years to 69.7. The SEYLLp index (per 100,000) increased to 776.8 years in 2016 (AAPC = 0.5%). The most unfavorable changes were observed in the group of women with secondary education. In 2004, the SEYLLp values started to grow at a rate of 2.3% and since 2011, they have been higher than amongst women with elementary education. In the years 2000-2016, the authors observed that SEYLLp was steadily declining (APC = -1.0%) in the group of inhabitants of rural areas, whereas with regards to city dwellers, the SEYLLp index has been increasing since 2004 (APC = 0.5%), which has resulted in increased disproportions regarding the place of residence. Conclusions The results of this study showed that breast cancer is becoming a serious epidemiological problem in Poland. There is the need to intensify activities among women at highest risk group and it should be the starting point for making key decision in combating breast cancer.